Revisiting the origins of Islamic glazed pottery: a technological examination of 8th-10th century AD ceramics from Islamic lands - Matin, M (2016)
The beginnings of Islamic ceramics have long been attributed to the opaque white glazed wares made in Iraq in the 9th century in response to the imported Chinese porcelain and stoneware. These Islamic glazes were known to have been opacified by tin-oxide and much work has been undertaken to characterise their development and spread. However, little has been done to explain the origins of this technology and its invention in Iraq. This thesis takes a new approach to investigating the beginnings of Islamic glazed pottery. It examines the technical aspects of early Islamic glazed wares from the 7th to 10th century AD from the Eastern Mediterranean to Central Asia. A significant number of sherds from Fustat, Aqaba, Al-Mina, Raqqa, Samarra, Basra, Kish, Susa, Nishapur, Merv and Samarqand were sampled and analysed using a scanning electron microscope equipped with energy dispersive spectroscopy (SEM-EDS). Particular focus was placed on the opaque yellow glazes from the Eastern Mediterranean and Mesopotamia (7th-9th century) and the opaque white glazes from Mesopotamia and Central Asia (9th -10th century). The analyses showed that the opaque yellow glazes and the opaque white glazes were respectively the result of lead-tin-oxide particles in high lead glazes, and tin-oxide particles in lead-alkali and alkali-lead glazes. Using experimental replication, it was found that at temperatures around 900°C, and in the presence of alkalis and alkaline earths, lead-tin-oxide particles convert to tin-oxide and that the colour of the glaze changes from yellow to white. It was therefore argued that the opaque yellow glazed wares of the 7th/8th-century Eastern Mediterranean represent a precursor to the opaque white glazed wares that flourished in Iraq in the 9th century. The results have helped change the way the beginnings of Islamic ceramics are viewed: origins in the 7th/8th century AD rather than the 9th century AD, first developed in Egypt or the Levant rather than Iraq, and indigenous rather than Chinese-inspired. The eastward spread of Islamic glazed wares to Iraq in the 9th century follows the move of the Islamic capital from Damascus, Syria, to Baghdad, Iraq, and the further spread of this technology east and west can now be traced.